Assessment of left ventricular function in chronic alcoholics by real-time three-dimensional echocardiography. Issue 5 (February 2017) - Wang, Yuanzheng; Shan, Guoxin; Shen, Jiaqi; Zhou, Qiao; Tan, Bijun; Liu, Yue; Luo, Runlan; Zhao, Shifen; Bi, Wenjun; Yao, Fangyi; Li, Guangsen
Abstract : Abstract: Chronic alcohol consumption may lead to progressive cardiac dysfunction. The aim of this study was to evaluate the feasibility of using real-time 3-dimensional echocardiography (3DE) on assessing left ventricular (LV) function in chronic alcoholics. We classified 92 male alcoholics into mild, moderate, and severe groups; 30 age-matched controls were also recruited. LV end-diastolic volume (LVEDV), LV end-systolic volume (LVESV), LV ejection fraction (LVEF), LV mass (LVM), LV mass index (LVMI), and systolic dyssynchrony index (SDI) were measured by 3DE and 2-dimensional echocardiography (2DE). Compared to the control group, LV volume and mass were higher in the moderate and severe alcoholic groups ( P  < 0.05). The severe alcoholic (symptomatic) group demonstrated decreased LVEF and increased SDI (detected by 3DE) ( P  < 0.05). Real-time 3DE can detect the increases of LV volumes and mass in asymptomatic alcoholics, and the changes of LVEF and systolic synchrony index in symptomatic alcoholics.